A dhwajastambh (flagpole) stands in the middle of Banganga Tank - Banganga by Ghosh, Ayan (2023)
In the middle of Banganga Tank stands a dhwajastambh (flagpole), which symbolizes Mount Meru, considered by Hindus to be the center of the physical, metaphysical, and spiritual universes. The water symbolizes the Cosmic Ocean, used in Hindu rituals performed on the ghats. The tank is also used for the immersion of ashes from the nearby crematorium.